2016
DOI: 10.1001/jama.2016.5951
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Protein-Based Risk Score for Cardiovascular Outcomes Among Patients With Stable Coronary Heart Disease

Abstract: Precise stratification of cardiovascular risk in patients with coronary heart disease (CHD) is needed to inform treatment decisions.OBJECTIVE To derive and validate a score to predict risk of cardiovascular outcomes among patients with CHD, using large-scale analysis of circulating proteins. DESIGN, SETTING, AND PARTICIPANTSProspective cohort study of participants with stable CHD. For the derivation cohort (Heart and Soul study), outpatients from San Francisco were enrolled from 2000 through 2002 and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
252
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(262 citation statements)
references
References 38 publications
8
252
1
1
Order By: Relevance
“…This resulted in accurate estimates of the REACH‐SMART model in the external validation sets. The discriminatory ability of the 3 models was moderate, which we considered acceptable, as this is in line with previous studies on models in patients with cardiovascular disease 4, 5, 29, 30…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This resulted in accurate estimates of the REACH‐SMART model in the external validation sets. The discriminatory ability of the 3 models was moderate, which we considered acceptable, as this is in line with previous studies on models in patients with cardiovascular disease 4, 5, 29, 30…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, this type of modeling does not account for survival up to the year of observation, which theoretically may result in biased estimates toward healthier survivors in very long‐term predictions. Third, the limited discriminatory ability of the SMART‐REACH model is comparable to previous risk scores for patients with clinically manifest vascular disease 4, 5, 29, 30. Previous studies have shown that additional risk factors are unlikely to result in relevant improvement 4, 38.…”
Section: Discussionmentioning
confidence: 74%
“…Using a targeted discovery proteomic platform, we were able to extend previous findings, demonstrate novel biomarker associations with incident CVD events, and validate previous genetic associations. Large‐scale mass spectrometry or newer aptamer‐based technology49, 50 may allow for profiling of many more proteins in large study samples that may refine current multimarker models. Further studies are needed to validate our findings and define clinical utility, with the ultimate goal of improving targeted strategies for CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…One of the many challenges is that fibrosis is a mechanism involved in a number of overlapping and/or coexisting risk and disease states and co‐morbidities48, 49 such as hypertension, chronic kidney disease, diabetes mellitus, obesity, atrial fibrillation, ischaemic heart disease, and prevalent HF, such that a number of circulating biomarkers can be present in these various conditions 26, 46, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61. Our hypothesis is that novel ‘mechanistic’ markers of cardiac fibrosis are differentially expressed in various risk and disease states and co‐morbidities.…”
Section: Discussionmentioning
confidence: 99%